Effect of Dietary Supplementation with Probiotic or Essential Oils on Growth Performance of Broiler Chickens - Chalghoumi , R.; Belgacem, A.; Trabelsi, I.; Bouatour, Y.; Bergaoui, R. (International Journal of Poultry Science, 2013)
This experiment was conducted to investigate the effect of the dietary supplementation of a probiotic (Lactobacillus plantarum strain TN8) or a commercial blend of essential oils (clove and cinnamon essential oils) on growth performance of broiler chicken. The dietary treatments were: basal diet as control (C); basal diet plus probiotic (0,2% of Lactobacillus plantarum strain TN8 at 2x1010 cfu/g; P); basal diet plus essential oils blend (300 mg/kg; EOB). A total of 900 one-day old male broiler chicks were randomly allocated to 3 experimental groups of 6 replicates of 50 chicks each. The chicks were grown to 35 d of age. Body weight, feed intake and feed conversion were weekly determined. The mortality was recorded daily. Concerning weight gain, in the periods of 8-14, 15-21 and 22-28 days of age, the group fed the essential oils blend presented significantly (p<0.05) higher values as compared with the other treatments. No statistical difference was detected in feed intake among treatments in any of the evaluated age intervals. Feed conversion ratio differences were detected only in the second period of 8-14 days of age, with the group fed the essential oils blend presenting statistically (p<0.05) lesser FCR as compared with that fed the probiotic product, which were not different from the control group. Mortality was different (p<0.05) only in the periods of 0-7 and 8-14 days of age, which was higher in the control group as compared with that of the birds fed the probiotic product and those fed the essential oils blend. At the end of the rearing period (35 days of age), the results showed that the dietary supplementation with probiotic or essential oils led to a significant improvement (p<0.05) in body weight gain and a numerical, but non significant (p>0.05) improvement in feed conversion in relation to the control group. Based on these results it can be concluded that probiotic strain and essential oils dietary supplementation have a growth promoting effect on broilers.